A Note on the Inverse Problem for a Fractional Parabolic Equation - Abdullah Said Erdogan; Hulya Uygun (Abstract and Applied Analysis)
For a fractional inverse problem with an unknown time-dependent source term, stability estimates are obtained by using operator theory approach. For the approximate solutions of the problem, the stable difference schemes which have first and second orders of accuracy are presented. The algorithm is tested in a one-dimensional fractional inverse problem.